A SEMANTIC ANALYSIS OF ANTONYMS IN SURAH AL-HADID OF THE QUR’AN BASED ON AL-KHAMMAS’S PERSPECTIVE - Al Faruqi, Mhd Ibnu Hanan; Agung, Muchammad Nuch Naufal; Hadri, Hadri; Firmansyah, Rizky (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2025)
This study aims to find out the types of antonyms contained in the Qur'an Surah Al-Hadid which consists of 29 verses. The background of this research departs from the importance of understanding semantic relationships in the Qur'an to deepen the interpretation and understanding of divine messages. The problem raised is how the form and function of antonyms in Surah Al-Hadid if analyzed through the Al-Khummas approach This research uses the library research method by utilizing secondary data in the form of journals, research reports, internet search results, and the Ottoman Rasam Qur'an. The analysis was carried out using the Al-Khammas approach which classifies antonyms into five types, namely tadhad had, tadhad mutadarrij, tadhad aksiy, tadhad amudy, and tadhad imtidadi. The results of the study show that in Surah Al-Hadid four types of antonyms are found, namely absolute antonyms, sideline antonyms, opposite antonyms, and straight-line antonyms. The four types of antonyms are spread across several verses and are categorized based on differences in their meaning. The data is presented in the form of a table that contains the verses and the types of antonyms contained in them. This research contributes to enriching the semantic study of the Qur'an through the application of the Al-Khammas approach which is still rarely used in linguistic analysis of the Qur'anic text.